2008
DOI: 10.1248/bpb.31.1215
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Studies on Plasma-to-Blood Ratio of Paclitaxel in Human, Rabbit and Rat Blood Fractions

Abstract: Many pharmacokinetic studies of paclitaxel formulations with or without Cremophor (CrEL) have been performed on experimental animals. However, limited studies describe the different pharmacokinetic behaviors of paclitaxel in animals. The different distribution of drug in blood fractions may have great effect on its pharmacokinetic behaviors. Our present study was designed to study the characteristics of paclitaxel distribution in human, rabbit and rat blood, by measuring plasma-to-blood ratio (PBR) of paclitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…PTX was measured in plasma and blood according to a previous report [22]. Briefly, an aliquot of 100  μ l plasma (or blood), 50  μ l docetaxel solution (10  μ g/mL, as an internal standard), and 2.5 mL acetonitrile were mixed using a vortex mixer for 30 s. The mixture was centrifuged at 3000 g for 10 min, then 2.0 mL supernatant was collected, and dried under a gentle stream of nitrogen gas at 50°C in a water bath.…”
Section: Methodsmentioning
confidence: 99%
“…PTX was measured in plasma and blood according to a previous report [22]. Briefly, an aliquot of 100  μ l plasma (or blood), 50  μ l docetaxel solution (10  μ g/mL, as an internal standard), and 2.5 mL acetonitrile were mixed using a vortex mixer for 30 s. The mixture was centrifuged at 3000 g for 10 min, then 2.0 mL supernatant was collected, and dried under a gentle stream of nitrogen gas at 50°C in a water bath.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of paclitaxel in SSL-PTX was determined by an HPLC method (26) by Waters HPLC system consisting of a 1525 pump and a 2487 ultraviolet detector (Waters Co. Inc., Westerville, OH, USA). Mobile phase consisted of methanol-water-tetrahydrofuran (67.5:30:2.5, v/v/v) and was delivered at a flow rate of 1 ml/min.…”
Section: Hplc Analysis Of Paclitaxelmentioning
confidence: 99%
“…This is due to paclitaxel being encapsulated into CrEL micelles and these micelles mainly exist in the water phase of the plasma. Our previous results showed that PVP, unlike CrEL, did not affect the distribution of paclitaxel in blood [13] . Many CrEL‐free paclitaxel formulations have been evaluated by comparing systemic exposure of paclitaxel in plasma with Taxol.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CrEL influences the distribution of paclitaxel in the blood of humans [12] and experimental animals [13] . By trapping paclitaxel in CrEL micelles, CrEL reduces the free paclitaxel fraction and changes the pharmacokinetic profile of paclitaxel [12] .…”
Section: Introductionmentioning
confidence: 99%